Handbook for developing emotional and social intelligence best practices, case studies, and strategies - Hughes, Marcia; Thompson, Henry L.; Terrell, James Bradford 1951- (Pfeiffer, 2009)
"Handbook for Developing Emotional and Social Intelligence is an authoritative collection of practical content--best practices, case studies, and tools--that showcases the application and development of emotional and social intelligence in the workplace. The authors are some of the best-known experts in the field and the book includes practitioners, academics and thought-leaders that contributed to this rich collection of knowledge and solutions that will appeal to anyone involved in developing leaders and teams. The handbook features topics such as leadership, recruitment, conflict resolution, team development, and stress management"--Resource description page
"Essential knowledge"--Page iii. - Includes bibliographical references and indexes. - Print version record
Keywords: Emotional intelligence; Social intelligence; Leadership; Executive coaching; Intelligence émotionnelle; Intelligence sociale; Accompagnement de gestionnaires; PSYCHOLOGY; Emotions; FAMILY & RELATIONSHIPS; Death, Grief, Bereavement; Führung; Sozialkompetenz